La investigación formativa en los estudiantes de la Carrera de Enfermería de la Universidad Estatal de Bolívar, Guaranda, periodo agosto – noviembre 2021 - Castillo Tubay, Evelyn Carla (2022)
Formative research constitutes a methodological tool that contributes to the improvement of students' knowledge about their professional and investigative preparation. However, despite knowing its benefits, there are still limitations in its implementation that limit the success of this activity. Next, the project called "TRAINING RESEARCH IN NURSING STUDENTS AT THE STATE UNIVERSITY OF BOLÍVAR, GUARANDA, PERIOD AUGUST - NOVEMBER 2021" The general objective was to evaluate the implementation of the formative research process in students of the nursing career at the State University of Bolívar, Guaranda, during the period August - November 2021. For this, a basic, non-experimental, descriptive research was carried out by means of which it seeks to publicize singularities about the object of study, in the field since a research questionnaire was applied to the population of the nursing career period August- November 2021 is a cross-sectional cohort that included a total of 248 people between teachers and students, the information that is processed with the use of the statistical software SPSS IBM version 25. A questionnaire was applied to each of the participants in order to define the level of knowledge about formative research, the level of implementation of the activity, the main advantages and limitations for its implementation and the knowledge they had about the projects that integrate knowledge and research hotbeds. Among the main results are moderately positive levels of implementation and knowledge about formative research. The limited time available to generate research was identified as limitations, and the advantages of having teaching tutors who cooperate in carrying it out, as well as the conviction offered by formative research in terms of generating knowledge about the profession. Also, the students still do not know about the management of the SPSS program, since it is an excellent software for information processing. It is concluded that there is a good level of knowledge, but it is not enough since a considerable percentage still does not know what formative research is and this was XVII reflected in the fact that the majority only use a single database, and that they do not know the different ones. forms that exist and can be applied in the nursing career, in addition, teachers should be trained on how to guide students in the elaboration of the Integrating Knowledge Projects (PIS), around the basic elements of Formative Research. Keywords: Nursing career; University teaching; Higher education; Formative research; Knowledge integrator program